Lumateperone (ITI−007) in the Treatment of Bipolar Depression: Results from a Randomized Clinical Trial. (April 2021) - D'Souza, Ian; Durgam, Suresh; Satlin, Andrew; Davis, Robert E.; Kozauer, Susan G.; Chen, Richard; Mates, Sharon; Calabrese, Joseph R
Abstract: Study Objective: Approved treatments for bipolar depression are limited and associated with a spectrum of undesirable side effects. Lumateperone (lumateperone tosylate, ITI−007), a mechanistically novel antipsychotic that simultaneously modulates serotonin, dopamine, and glutamate neurotransmission, is FDA-approved for the treatment of schizophrenia. Lumateperone is currently being investigated for the treatment of bipolar depression (major depressive episodes [MDE] associated with bipolar I and bipolar II disorder). This Phase 3 randomized, double-blind, parallel-group, placebo-controlled multinational study (NCT03249376) investigated the efficacy and safety of lumateperone in patients with bipolar I or bipolar II disorder experiencing a MDE. Method: Patients (18 75 years) with a clinical diagnosis of bipolar I or bipolar II disorder who were experiencing a MDE (Montgomery-Åsberg Depression Rating Scale [MADRS] Total score =20 and a Clinical Global Impression Scale-Bipolar Version-Severity [CGI-BP-S] score =4 at screening and baseline) were randomized to lumateperone 42mg or placebo for 6 weeks. The primary and key secondary efficacy endpoints were change from baseline to Day 43 in MADRS total score and CGI-BP-S scores, respectively. Secondary efficacy outcomes included response (MADRS improvement = 50%) and remission (MADRS total score =12) at Day 43. Safety assessments included treatment emergent adverse events, laboratory parameters, vital signs, extrapyramidal symptoms (EPS), and suicidality. Results: In this study, 377 patients received treatment (placebo, n=189; lumateperone 42mg, n=188) and 333 completed treatment. Patients in the lumateperone 42-mg group had significantly greater mean improvement on MADRS total score change from baseline to Day 43 compared with placebo (least squares mean difference [LSMD]=-4.6; 95% confidence interval [CI]=-6.34, −2.83; effect size vs placebo [ES]=-0.56; P<.0001). Lumateperone treatment was associated with significant MADRS improvement in both patients with bipolar I (LSMD=-4.0; 95% CI=-5.92, −1.99; ES=-0.49; P<.0001) and bipolar II (LSMD=-7.0; 95% CI=-10.92, −3.16; ES=-0.81; P=.0004). The lumateperone 42-mg group also had significantly greater mean improvement in CGI-BP-S total score compared with placebo (LSMD=-0.9; 95% CI=-1.37, −0.51; ES=-0.46; P<.001). Lumateperone compared with placebo had significantly greater MADRS response rate (51.1% vs 36.7%; odds ratio=2.98; P<.001) and remission rates (P=.02) at Day 43. Lumateperone treatment was well tolerated, with minimal risk of EPS, metabolic, and prolactin side effects. Conclusions: Lumateperone 42 mg significantly improved depression symptoms in both patients with bipolar I and bipolar II depression. Lumateperone was generally well tolerated. These results suggest that lumateperone 42 mg may be a promising new treatment for bipolar depression associated with bipolar I or bipolar II disorder. Funding: Intra-Cellular Therapies, Inc.